HUBUNGAN ANTARA PARITAS DAN USIA IBU BERISIKO DENGAN KEJADIAN PREEKLAMSIA PADA IBU HAMIL - Az-Zahra, Aura Fatimah; Sasmito, Lulut; Maryanti, Syiska Atik (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
Preeclampsia is one cause of MMR in the world. The preeclampsia incidence in Indonesia 2022 (22.42%), is the cause of maternal death. The preeclampsia incidence in East Java 2022 (14,128 peoples), while in Jember Regency (936 peoples). The purpose of this study to find out the relationship between the risk parity and age of at-risk mothers with the incidence of preeclampsia in pregnant women in the Sumbersari Public Health Center in 2023. The designs used correlation analysis with retrospective uses quota sampling technique. Data were obtained from the maternal cohort and observation sheet instruments using a statistical test of contingency coefficient. The test result using contingency coefficient obtained a weak relationship of 29% (p-value 0,038 < ? 0,05) is relationship between the risk parity with the preeclampsia incidence and a weak relationship of 35% (p-value 0,009 < ? 0,05) is relationship between the age of the at-risk mother with the preeclampsia incidence. Therefore, researchers suggest that cooperation between health workers and pregnant women can be carried out well because with ANC, preeclampsia screening can be routinely carried out.